A comparative analysis of human plasma and serum proteins by combining native PAGE, whole‐gel slicing and quantitative LC‐MS/MS: Utilizing native MS‐electropherograms in proteomic analysis for discovering structure and interaction‐correlated differences. Issue 24 (26th September 2017) - Wen, Meiling; Jin, Ya; Manabe, Takashi; Chen, Shumin; Tan, Wen
Abstract: MS identification has long been used for PAGE‐separated protein bands, but global and systematic quantitation utilizing MS after PAGE has remained rare and not been reported for native PAGE. Here we reported on a new method combining native PAGE, whole‐gel slicing and quantitative LC‐MS/MS, aiming at comparative analysis on not only abundance, but also structures and interactions of proteins. A pair of human plasma and serum samples were used as test samples and separated on a native PAGE gel. Six lanes of each sample were cut, each lane was further sliced into thirty‐five 1.1 mm × 1.1 mm squares and all the squares were subjected to standardized procedures of in‐gel digestion and quantitative LC‐MS/MS. The results comprised 958 data rows that each contained abundance values of a protein detected in one square in eleven gel lanes (one plasma lane excluded). The data were evaluated to have satisfactory reproducibility of assignment and quantitation. Totally 315 proteins were assigned, with each protein assigned in 1–28 squares. The abundance distributions in the plasma and serum gel lanes were reconstructed for each protein, named as "native MS‐electropherograms". Comparison of the electropherograms revealed significant plasma‐versus‐serum differences on 33 proteins in 87 squares (fold difference > 2 or < 0.5, p < 0.05). Many of the differences matched with accumulated knowledge on protein interactions and proteolysis involved in blood coagulation, complement and wound healing processes. We expect this method would be useful to provide more comprehensive information in comparative proteomic analysis, on both quantities and structures/interactions.